Penegakan Hukum Pidana terhadap Pelaku Tindak Pidana Penjual Pangan Kedaluwarsa di Tinjau dari Undang-Undang Nomor 18 Tahun 2012 tentang Pangan di Kelurahan Lasiana, Kecamatan Kelapa Lima, Kota Kupang - Juliet Larasati Anggeliq Nugroho; Deddy R. Ch. Manafe; Adrianus Djara Dima (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This study aims to find out and analyze the Enforcement of Criminal Law Against Perpetrators of Expired Food Sellers in Review of Law Number 18 of 2012 concerning Food in Lasiana Village, Kelapa Lima District, Kupang City. This study is an empirical judicial research that is analyzed in a qualitative descriptive manner using primary legal materials and secondary legal materials obtained using interview, observation and documentation techniques. The results of this study show that (1) law enforcement against the sale of expired food in Lasiana Village is still not optimal (2) efforts to overcome the sale of expired food in Lasiana Village have been carried out through several approaches, but still need to increase effectiveness.